Women’s subordination in premarital pregnancy - Ni Made Tantri Chandra; Emy Susanti; Karen Mwende Kinuthia (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The presence of patriarchal culture can be found in most regions of Indonesia, including Bali. The patriarchal culture in Bali tends to be more rigid because of the Balinese belief that any offspring, especially men, will not only continue the responsibilities of the parents in terms of the social life of the community; however, they also expected to carry out the ceremonies of death for their parents. They are trusted to help their parents reach the creator easily. The Balinese culture has been dominated by patriarchy for a long time and has continued developing to this day. Patriarchal power is increasingly persistent when it comes to power in Bali. As a result, women in Bali are still considered subordinate creatures under the patriarchy’s control and bondage. The phenomenon of premarital pregnancy in Bali is a reflection of the new way that men dominate women. The approach used in this study is Michel Foucault’s theory of power. The method used was qualitative research with in-depth interviews with 18 informants who were native Balinese. This research was conducted in Denpasar, Singaraja, and Badung City. The results of this study found that the social reality of premarital pregnancy in the urban areas of Bali’s Island is inseparable from the influence of the social discourse behind the apparent reality. The discourse then obtains the legitimacy of truth from the family and produces new knowledge to believe the truth. In this social reality, premarital pregnancy has made Balinese women significantly disadvantaged and increasingly subordinated.